Pengaruh Kecerdasan Emosional (EQ), Kecerdasan Spiritual (SQ), Perilaku Belajar Dan Metode Mengajar Dosen Terhadap Tingkat Pemahaman Akuntansi Mahasiswa Prodi Akuntansi : Studi Kasus Pada Universitas Islam Majapahit Mojokerto Dan STIE AMM Mataram - Hari Setiono; Muhammad Bahril Ilmiddaviq; Agus Khazin Fauzi; Nur Ainiyah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
This study aims to examine the effect of emotional quotient, spiritual quotient, learning behavior and teaching methods of lecturers on the level of understanding of student accounting. This research was conducted on undergraduate students of the Accounting Study Program, Faculty of Economics at Islamic University of Majapahit and STIE AMM Mataram. This type of research is associative quantitative research. The population used in this study were all accounting study program students, totaling 1.460 respondents. The sample used was 100 respondents with Slovin formula as the sampling technique. Data collection techniques using a questionnaire, with a Likert scale as a measuring tool. Data analysis in this study was linear regression analysis with the help of SmartPLS version 3.0 software. The results of this study indicate that emotional intelligence has no significant positive effect on the level of understanding of accounting, spiritual intelligence has a significant positive effect on the level of understanding of accounting, learning behavior has a significant positive effect on the level of understanding of accounting. accounting, lecturer teaching methods have no significant positive effect on the level of understanding of accounting.